SELISIH BIAYA PRODUKSI SEBAGAI ALAT PENGENDALIAN MANAJEMEN PT INDO PUSAKA BERAU (ACCOUNTING STUDY PROGRAM, UNIVERSITAS MUHAMMADIYAH BERAU, 2019)
This study aims to analyze whether the difference that occurs in the cost of raw materials, direct labor, and factory overhead costs between the standard costs and the actual costs in PLTU LATI is a difference that is favorable or unfavorable. Data collection techniques with field research and library research. The analytical tool used is the analysis of the difference in raw material costs, the difference in direct labor costs and the difference in factory overhead costs. The hypothesis in this study is that the difference allegedly occurs in the cost of raw materials, direct labor costs, and factory overhead costs at PT Indo Pusaka Berau Tanjung Redeb is a favorable difference. The results showed that the difference in the cost of producing MWh electricity at PT Indo Pusaka Berau Tanjung Redeb in 2018, namely the difference in the price of raw material costs Rp. 548,029.80, - is favorable, the difference in quantity of raw materials is Rp. 957,216,602, - is (favorable) , the difference in direct labor costs Rp 2,602,642,084, - is (unfavorable), and the difference in factory overhead costs Rp 8,807,051,422, - is (favorable) This shows that the difference in the overall production cost budget is favorable or profitable. This beneficial difference shows that the company is really able to reduce production costs optimally in 2018.